A z‐gradient array for simultaneous multi‐slice excitation with a single‐band RF pulse. Issue 1 (4th December 2017) - Ertan, Koray; Taraghinia, Soheil; Sadeghi, Alireza; Atalar, Ergin
Abstract : Purpose: Multi‐slice radiofrequency (RF) pulses have higher specific absorption rates, more peak RF power, and longer pulse durations than single‐slice RF pulses. Gradient field design techniques using a z‐gradient array are investigated for exciting multiple slices with a single‐band RF pulse. Theory and Methods: Two different field design methods are formulated to solve for the required current values of the gradient array elements for the given slice locations. The method requirements are specified, optimization problems are formulated for the minimum current norm and an analytical solution is provided. A 9‐channel z‐gradient coil array driven by independent, custom‐designed gradient amplifiers is used to validate the theory. Results: Performance measures such as normalized slice thickness error, gradient strength per unit norm current, power dissipation, and maximum amplitude of the magnetic field are provided for various slice locations and numbers of slices. Two and 3 slices are excited by a single‐band RF pulse in simulations and phantom experiments. Conclusion: The possibility of multi‐slice excitation with a single‐band RF pulse using a z‐gradient array is validated in simulations and phantom experiments. Magn Reson Med 80:400–412, 2018. © 2017 International Society for Magnetic Resonance in Medicine.